Effect of Childhood Trauma on Emotion Regulation Among Adults in Malaysia - Perveen, Asma; Shang Hua, Gabriel Thai (University of Wah Journal of Social Sciences, 2021)
The primary objective of the current study is to identified the predicting effect of childhood trauma on emotional regulation among adults in Malaysia. Different types of childhood trauma were included in the study which comprises of emotional abuse, physical abuse, sexual abuse, emotional neglect and physical neglect. As for emotion regulation strategies, it includes cognitive reappraisal and expressive suppression. A cross-sectional survey method was adopted as the study design. An online survey which consists of instruments of measurement Childhood Trauma Questionnaire, and Emotion Regulation Questionnaire was distributed through social media. A total of sample size of 390 (Male = 207, Female = 183) (Age range= 21-40) participated in the study. The findings indicated that there is a significant predicting effect (p<0.005) of childhood trauma on emotional regulation among adults in Malaysia. Each type of childhood trauma was found to have a significant relationship with emotion dysregulation which might can lead to potential development of psychopathology. The current study identified that childhood trauma affects the emotion regulation ability to deal with any stressors. The findings are crucial for professionals and clinicians to better understand the phenomena of childhood trauma and emotional regulations.